Use of Conceptual Metaphors in Miguna Miguna’s Political Commentaries on Facebook in Kenya: A Conceptual Metaphor Perspective - WAHOME, MAINA; Nurhayati, Nurhayati (Master Program in Linguistics, Diponegoro University, 2023)
This paper examines Miguna's political commentaries on Facebook, which have become a potent force in Kenya's socio-political discourse. Known for his incisive and metaphor-laden commentaries, Miguna, popularly called